2016
DOI: 10.1074/jbc.m116.745596
|View full text |Cite
|
Sign up to set email alerts
|

The Amino-terminal Domain of the Androgen Receptor Co-opts Extracellular Signal-regulated Kinase (ERK) Docking Sites in ELK1 Protein to Induce Sustained Gene Activation That Supports Prostate Cancer Cell Growth

Abstract: The ETS domain transcription factor ELK1 is in a repressive association with growth genes and is transiently activated through phosphorylation by ERK1/2. In prostate cancer (PCa) cells the androgen receptor (AR) is recruited by ELK1, via its amino-terminal domain (A/B), as a transcriptional co-activator, without ELK1 hyper-phosphorylation. Here we elucidate the structural basis of the interaction of AR with ELK1. The ELK1 polypeptide motifs required for co-activation by AR versus those required for activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 58 publications
(65 reference statements)
0
32
0
Order By: Relevance
“…To delineate the mechanism behind its distinct expression in these cells we analyzed the AIRE promoter region for the binding sites of various other transcription factors. Recently, transcription factor Elk-1 which belongs to Ets family of transcription factors has been shown to be associated with prostate cancer progression 21 , 22 . Elk-1 is also known to be accessory and supportive for AR transcriptional signaling 23 .…”
Section: Resultsmentioning
confidence: 99%
“…To delineate the mechanism behind its distinct expression in these cells we analyzed the AIRE promoter region for the binding sites of various other transcription factors. Recently, transcription factor Elk-1 which belongs to Ets family of transcription factors has been shown to be associated with prostate cancer progression 21 , 22 . Elk-1 is also known to be accessory and supportive for AR transcriptional signaling 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Under androgen deprivation, we found that the most enriched motif corresponded to ELK1 (Fig 8A). ELK1 is an ETS transcription factor and AR co-regulator that promotes growth in prostate cancer cells and regulates ligand-independent recruitment of AR to chromatin through interaction with the AR NTD [23, 24]. Interestingly, also enriched under androgen deprivation, as well as with androgen treatment, were several other members of the ETS family of transcription factors (Fig 8A and S12A Fig).…”
Section: Resultsmentioning
confidence: 99%
“…ELK1 is an ETS transcription factor that controls AR transcriptional activity and promotes prostate cancer progression [20, 23, 24]. ELK1 has also been shown to interact directly with the AR ligand-independent N-terminal transcriptional activation domain [23, 24]. Given the increase in H3K27 acetylation at the MAOA promoter with MED19 overexpression, it is possible that MED19, in conjunction with ELK1, could promote recruitment of HATs, such CBP and p300, which are also known AR co-regulators [10–12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations